Glutamatergic and neural dysfunction in postpartum depression using magnetic resonance spectroscopy. (30th July 2017) - Rosa, Carlos E.; Soares, Jair C.; Figueiredo, Felipe P.; Cavalli, Ricardo C.; Barbieri, Marco A.; Schaufelberger, Maristela S.; Salmon, Carlos E.G.; Del-Ben, Cristina M.; Santos, Antonio C.
Abstract: Although postpartum depression (PPD) is a prevalent subtype of major depressive disorder, neuroimaging studies on PPD are rare, particularly those identifying neurochemical abnormalities obtained by proton magnetic resonance spectroscopy (¹H-MRS). The dorsolateral prefrontal (DLPF) and the anterior cingulate gyrus (ACG) are part of the neural pathways involved in executive functions and emotional processing, and both structures have been implicated in the neurobiology of depressive disorders. This study aimed to evaluate brain metabolites abnormalities in women with PPD compared with healthy postpartum (HP) women. Thirty-six PPD (34 without antidepressants) and 25 HP women underwent a ¹H-MRS acquired on a 3-T MRI system, with the volume of interest positioned in ACG and DLPF. An ANCOVA was conducted with age, postpartum time, and contraceptive type as covariates. PPD group presented significantly lower Glutamate+Glutamine (Glx, −0.95 mM) and N-acetylaspartate+N-acetylaspartylglutamate (NAA, −0.60 mM) values in DLPF. There were no significant differences between groups in ACG, but we found a significant increase of Glutamate (Glu, 2.18 mM) and Glx (1.84 mM) in participants using progestogen-only contraceptives. These findings suggest glutamatergic dysfunction and neuronal damage in the DLPF of PPD patients, similarly to other subtypes of depressive disorders. Progestogens seem to interfere in the neurochemistry of ACG. Highlights: PPD is highly prevalent subtype of MDD related to damage for the whole family. Postpartum depression is related to abnormalities neurochemistry in the dlPFC. The PPD group presented decrease of Glx and NAA levels compared to HP group. The dlPFC abnormalities are related to glutamatergic dysfunction and damage. Progestogen-only contraceptive use lead to increased Glu e Glx in the ACG.